Representation of Ocean-Atmosphere Processes Associated with Extended Monsoon Episodes over South Asia in CFSv2 - Mohan, T. S.; Annamalai, H.; Marx, Larry; Huang, Bohua; Kinter, James (Frontiers in Earth Science, 2018)
In the present study, we analyze 30-years output from free run solutions of CFSv2 coupled model to assess the model’s representation of extended (>7 days) active and break monsoon episodes over south Asia. Process based diagnostics is applied to the individual and composite events to identify precursor signals in both ocean and atmospheric variables. Our examination suggests that CFSv2, like most coupled models, depict systematic biases in variables important for ocean-atmosphere interactions. Nevertheless, model solutions capture many aspects of monsoon extended break and active episodes realistically, encouraging us to apply process-based diagnostics. Diagnostics reveal that sea surface temperature (SST) variations over the northern Bay of Bengal where the climatological mixed-layer is thin, lead the in-situ precipitation anomalies by about 8 (10) days during extended active (break) episodes, and the precipitation anomalies over central India by 10-14 days. Mixed-layer heat budget analysis indicates for a close correspondence between SST tendency and net surface heat flux (Q_net). MSE budgets indicate that horizontal moisture advection to be a coherent precursor signal (~10 days) during both extended break (dry advection) and active (moist advection) events. The lead timings in these precursor signals in CFSv2 solutions will be of potential use to monitor and predict extended monsoon episodes. Diagnostics, however, also indicate that for about 1/3 of the identified extended break and active episodes, inconsistencies in budget terms suggest precursor signals could lead to false alarms. Apart from false alarms, compared to observations, CFSv2 systematically simulates a greater number of extended monsoon active episodes.